2017
DOI: 10.3389/fimmu.2017.00542
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Induction of Heme Oxygenase-1 Expression Is Dependent on Oxidative Stress and Reflects Treatment Outcomes

Abstract: The antioxidant enzyme heme oxygenase-1 (HO-1) is implicated in the pathogenesis of tuberculosis (TB) and has been proposed as a biomarker of active disease. Nevertheless, the mechanisms by which Mycobacterium tuberculosis (Mtb) induces HO-1 as well as how its expression is affected by HIV-1 coinfection and successful antitubercular therapy (ATT) are poorly understood. We found that HO-1 expression is markedly increased in rabbits, mice, and non-human primates during experimental Mtb infection and gradually de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 70 publications
2
48
0
Order By: Relevance
“…A number of prospective studies have previously reported changes in biomarker levels during antitubercular treatment in either pulmonary or extrapulmonary TB cases [15,30,33,35,37,[39][40][41][49][50][51]. Our study adds to the current knowledge in the field by directly comparing these changes between PTB and EPTB disease forms while focusing on both lipid mediators and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…A number of prospective studies have previously reported changes in biomarker levels during antitubercular treatment in either pulmonary or extrapulmonary TB cases [15,30,33,35,37,[39][40][41][49][50][51]. Our study adds to the current knowledge in the field by directly comparing these changes between PTB and EPTB disease forms while focusing on both lipid mediators and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 86%
“…Studying plasma biomarkers in the context of TB may provide important insights into diagnosis, treatment efficacy and also disease pathogenesis [33]. Several prior studies have reported concentrations of cytokines, chemokines, acute phase proteins and lipid mediators in populations of pulmonary TB patients [30,[34][35][36][37][38][39][40][41], but less is known about extrapulmonary infection [42][43][44]. Here, we performed multiparametric analyses of plasma concentrations of several inflammatory cytokines, soluble cytokine receptors, receptor ligands, alongside with lipid mediators in a large set of active TB patients with pulmonary or extrapulmonary disease to characterize the systemic inflammatory profile of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the plasma level of HMOX1 was proposed as a biomarker capable of differentiating patients with active disease from those with latent infection or those who have undergone treatment against TB . The correlation of HMOX1 expression with TB disease was also demonstrated in various animal models such as rabbits, mice, and primates . Nevertheless, more studies are required to delineate the role of HMOX1 in the pathogenesis of mycobacterial infections.…”
Section: Bacterial Infectionsmentioning
confidence: 99%